Digital transformation of the textile process chain – state-of-the-art - Robert Nafz; Caroline Schinle; Christian Kaiser; Yordan K. Kyosev (Communications in Development and Assembling of Textile Products)
New digital technologies, the internet age, and ever-increasing customer expectations are changing industries worldwide. Companies in the apparel industry must digitally transform to remain competitive. Traditional approaches will no longer work in the face of change because digital transformation is inevitable, irreversible, enormously fast, and unfortunately marked by challenges in implementation and uncertainties in execution. However, it also brings many benefits for which it is worth striving for the complete digitization of the value chain. This research paper aims to clarify the benefits and challenges companies face in digital transformation. For this purpose, it shows a report on the current state of digitalization in the apparel industry. The article ends with an approach on the implementation of digitization in the apparel companies.